Potential Storage Methods to Maintain the Quality of Local Bangka Rice Seeds - Marini Marini; Eries Dyah Mustikarini; Kartika Kartika (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2025)
The success of rice production is partly determined by the quality of the seeds used. The main challenge in maintaining seed quality is proper management to ensure that seeds remain preserved during storage. This study aims to evaluate the effect of storage methods on the quality of local Bangka rice seeds, as well as the chemical composition of the seeds after being stored for 8 months. The research period is from February to December 2024, conducted at the Seed Laboratory and Plant Breeding of the Bangka Belitung University. The study uses an experimental design of a Completely Randomized Design in a split-plot pattern. The first factor consists of 6 accessions of local Bangka rice (Mukot, Jawa, Ungu, Pulut Hitam, Balok Merah, and Mayang Hutan). The second factor consists of 7 storage media (cans, 40-micron plastic, 120-micron plastic, plastic sacks, plastic jars, seed trays, and panicles). Each treatment was repeated 4 times. The results show that the Balok Merah accession exhibited the best performance, supported by the highest maximum growth potential, germination rate, vigor index, uniformity of growth, and normal seedling dry weight, along with more consistent moisture content. The panicle storage medium showed the best results in maintaining seed quality during storage, supported by the highest maximum growth potential and germination rate. The best treatment combination was the storage with panicles of the Jawa accession, supported by germination rate and the highest maximum growth potential. Proximate analysis indicated that the highest moisture content, ash content, and protein levels were found in Balok Merah. The highest fat content was in the Pulut Hitam accession, while the highest carbohydrate content was in the Mukot accession. There was a strong positive correlation between maximum growth potential and germination rate.